2008
DOI: 10.1111/j.1365-2141.2007.06971.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute megakaryoblastic leukaemia (AMKL) in children: a comparison of AMKL with and without Down syndrome

Abstract: SummaryTo characterize childhood acute megakaryoblastic leukaemia (AMKL), we reviewed 45 children with AMKL diagnosed between 1986 and 2005 at Nagoya University Hospital and Japanese Red Cross Nagoya First Hospital. Twenty-four patients (53%) had AMKL associated with Down syndrome (DS-AMKL) and 21 (47%) had non-DS-AMKL. The median age of the DS-AMKL patients was 21 months (range, 8-38 months) and that of non-DS-AMKL patients was 15 months (range, 2-185 months). The morphology of blast cells was categorized int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
79
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 41 publications
8
79
3
Order By: Relevance
“…The median age at diagnosis was 1 year, which was lower than that in the total group of children with AML (13 years) and also lower than what is reported in literature [6,8,11].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…The median age at diagnosis was 1 year, which was lower than that in the total group of children with AML (13 years) and also lower than what is reported in literature [6,8,11].…”
Section: Discussioncontrasting
confidence: 63%
“…The incidence of AMKL varies between 7.1 and 19.1% of AML cases in children [3,[6][7][8]. Recently, Hama et al have reported much higher incidence of AMKL at 23.2% in Japan [11]. This may indicate that the reported incidence of AMKL in our series may be an underestimation probably due to the difficulties of diagnosis.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Similar cases are also observed in cells carrying trisomy 21 in mosaic models [12], suggesting that a cell-autonomous program provoked by the GATA1 mutation and trisomy 21 contributes to the onset of TAM. Relatively few cases of AMKL harboring mutations in the GATA1 gene exist in the absence of trisomy 21 [13,14]. Therefore, the pathogenesis of TAM seems to be closely associated with GATA1 dysfunction in combination with the impact provided by the extra chromosome 21.…”
Section: Ds-associated Amklmentioning
confidence: 99%